Peran Komitmen Organisasi, Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Pengadilan Negeri Boyolali Kelas 1B - Saskia Anggun Choirunnisa; Khabib Alia Akhmad; Agus Suyatno (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research aims to determine and explain the influence of organizational commitment, work discipline, and work motivation on the performance of Class 1B Boyolali District Court employees. The number of samples used in this research was 40 respondents. The method used is a quantitative method. Data analysis techniques use SEM-PLS and SmartPLS 4.0. The results of this research show that organizational commitment has a positive and significant effect on performance, work discipline has a positive and significant effect on performance, work motivation has a positive and significant effect on performance.